2019
DOI: 10.1200/jco.2019.37.15_suppl.6536
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life, satisfaction and cost of care in metastatic colorectal cancer patients receiving ambulatory chemotherapy.

Abstract: 6536 Background: Colorectal cancer is an important health problems in Thailand; chemotherapy remains the most suitable treatment for metastatic patients. Chemotherapy treatment that was once delivered only in hospital environments is now administered at patient's home that helping patients to live normal lives during receiving chemotherapy. The chemotherapy regimens are based on a 48 hours 5-fluorouracil infusion combined that need patients to be hospitalized, consequence to decrease QOL and increase cost of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…QALYs was used as the measure of health outcomes and was calculated from the utility score (quality‐of‐life weight) multiplied by a 6‐month time horizon (12‐cycle cancer treatment). Utility scores were calculated based on the Functional Assessment of Cancer Therapy‐Colorectal score and these data were collected from patients diagnosed with colorectal cancer at the Ramathibodi Hospital 6,11 . AE rates associated with HC and IP were collected from the electronic medical records of HC and IP patients.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…QALYs was used as the measure of health outcomes and was calculated from the utility score (quality‐of‐life weight) multiplied by a 6‐month time horizon (12‐cycle cancer treatment). Utility scores were calculated based on the Functional Assessment of Cancer Therapy‐Colorectal score and these data were collected from patients diagnosed with colorectal cancer at the Ramathibodi Hospital 6,11 . AE rates associated with HC and IP were collected from the electronic medical records of HC and IP patients.…”
Section: Methodsmentioning
confidence: 99%
“…When the medication is complete, the pump can be removed via an outpatient visit. 5,6 Thus, for patients receiving the mFOLFOX6 regimen, there is no need for hospitalization. The previous study showed that the implementation of HC has substantially improved patients' quality of life and their satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations